The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1645/16-125
|View full text |Cite
|
Sign up to set email alerts
|

Egg-Hatching Mechanism of Human Liver Fluke,Opisthorchis viverrini: A Role For Leucine Aminopeptidases From the Snail Host,Bithynia siamensis goniomphalos

Abstract: The human liver fluke Opisthorchis viverrini (Platyhelminthes, Trematoda, Digenea) uses snails of the genus Bithynia as first intermediate host. Peculiarly among trematodes, the eggs of O. viverrini hatch within the digestive tract of its snail host. It remains uncertain whether hatching in this species is mediated through mechanical fracture of the eggshell or by digestion with specific digestive enzymes. This study aimed to characterize enzymes with specific inhibitors and factors involved in the hatching ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Ubenimex is one of LAP inhibitors that can reduce the activity of LAP, and therefore it can reduce the digestion of liver tissues, fibrogenesis and infiltrative growth (8,47,48). It has also reported that Ubenimex can reduce the invasiveness and damage of other parasites like Leishmania, Human liver fluke, plasmodium by inhibiting the LAP proteins levels (27,49,50). In some malignant tumors, Ubenimex can also inhibit the migration and invasion by alleviating the activity of the LAP (CD13)/NAB1/MAPK pathway (51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…Ubenimex is one of LAP inhibitors that can reduce the activity of LAP, and therefore it can reduce the digestion of liver tissues, fibrogenesis and infiltrative growth (8,47,48). It has also reported that Ubenimex can reduce the invasiveness and damage of other parasites like Leishmania, Human liver fluke, plasmodium by inhibiting the LAP proteins levels (27,49,50). In some malignant tumors, Ubenimex can also inhibit the migration and invasion by alleviating the activity of the LAP (CD13)/NAB1/MAPK pathway (51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…Egg hatching is a complex process that involves multiple synergies including neuronal activity, hormone secretion, protease synthesis and energy metabolism (Khampoosa et al, 2018; Konopová et al, 2020). Injecting corticotropin‐releasing hormone into the egg embryos of domestic chickens ( Gallus gallus ) results in the release of adrenocorticosteroids and thyroid hormones, speeding up egg hatching (Watanabe et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Egg hatching is a complex process that involves multiple synergies including neuronal activity, hormone secretion, protease synthesis and energy metabolism (Khampoosa et al, 2018;Konopová et al, 2020). Injecting F I G U R E 7 The putative pathway that the circadian clock regulates hatching rhythm of silkworm.…”
Section: Discussionmentioning
confidence: 99%